The effect of the level of Islamicity performance index on the financial performance of Islamic banks - Gunarianto Gunarianto; Muhammad Attar Indra Rajasa; Indri Supriani (Universitas Islam Negeri Walisongo Semarang, 2024)
Purpose - This study examines the effects of the Islamicity Performance Index (IPI) on Muamalat Indonesia's financial performance, specifically focusing on its adherence to sharia governance, sharia compliance, and sharia social indicators.Method - The study employs a quantitative methodology, notably utilizing Autoregressive Distributed Lag statistical technique to examine secondary data. The dataset comprises quarterly time series data encompassing the period from the initial quarter of 2013Q1 to the conclusion of 2023Q2.Result - Equitable Distribution Ratio exerts a positive impact on financial performance, while Profit-Sharing Ratio demonstrates a deleterious effect. In contrast, the Zakat Performance Ratio and the comparison between Islamic Income and Non-Islamic Income do not demonstrate statistically significant effects.Implication - These findings emphasize the need to improve the usefulness of IPI in enhancing financial outcomes for Islamic financial institutions by addressing obstacles. The study provides insights into the difficulties faced by Islamic banks when implementing profit-sharing financing methods, while also emphasizing the significant impact of Equitable Distribution Ratios on enhancing financial performance.Originality - This study not only examines a single element of financial ratios, as previous study has done, additionally combines two crucial ratios: ROA and ROE. The use of ARDL) also offers a more detailed elucidation of the correlation between these variables.